Attribution of Neuropsychiatric Manifestations to Systemic Lupus Erythematosus - Bortoluzzi, Alessandra; Scirè, Carlo Alberto; Govoni, Marcello (Frontiers in Medicine, 2018)
Neuropsychiatric (NP) involvement in Systemic Lupus Erythematosus (SLE) is one of the most severe manifestations of the disease that has a heavy impact on patient's functioning, quality of life and disease outcome. The prevalence is highly variable and the clinical phenotypes vary from common syndromes to rare NP entities. Its occurrence may be the result of a primary manifestation of SLE, secondary to other conditions (such as infections or metabolic disturbances) or the effect of concomitant comorbidities that often complicate the disease course. Correct attribution of NP events may pose diagnostic challenges and it is a critical factor in selecting the correct management. Although there is still no diagnostic gold standard to rightly diagnose NPSLE syndromes, great advances have been made in improving the clinician judgment in the evaluation process. In this narrative review, we present and discuss available evidence concerning NPSLE with a special focus on the attribution models developed using composite decision rules to ascribe NP events to SLE.